2021
DOI: 10.1016/j.polymer.2021.123643
|View full text |Cite
|
Sign up to set email alerts
|

Engineering laminated paper for SARS-CoV-2 medical gowns

Abstract: The COVID-19 pandemic has highlighted the need for diversity in the market and alternative materials for personal protective equipment (PPE). Paper has high coatability for tunable barrier performance, and an agile production process, making it a potential substitute for polyolefin-derived PPE materials. Bleached and newsprint papers were laminated with polyethylene (PE) coatings of different thicknesses, and characterised for their potential use as medical gowns for healthcare workers and COVID-19 patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This elution was plate counted and it was found that there were zero detectable viral phage counts. This result points to the finding that destruction of the captured Φ174 bacteriophage droplet particle was completed [ 33 , 34 ]. PhiX174 was used as a surrogate virus for SARS-CoV-2 to observe oxidation.…”
Section: Discussion: Molekule Devices To Manage Covid-19 In...supporting
confidence: 71%
See 1 more Smart Citation
“…This elution was plate counted and it was found that there were zero detectable viral phage counts. This result points to the finding that destruction of the captured Φ174 bacteriophage droplet particle was completed [ 33 , 34 ]. PhiX174 was used as a surrogate virus for SARS-CoV-2 to observe oxidation.…”
Section: Discussion: Molekule Devices To Manage Covid-19 In...supporting
confidence: 71%
“…PhiX174 was used as a surrogate virus for SARS-CoV-2 to observe oxidation. The Φ174 bacteriophage has a polyhedral morphology with high assay sensitivity, rapid growth, and high titer, and has a limit of detection that approaches a single virus particle [33] , [34] , [35] . Both Corona virions (including SARS-CoV-2) and Φ174 bacteriophage have proteins (capsid and spiked proteins) and genomic materials that have C—C, C—H, and C—N bonds, and the test and swatch analysis demonstrate that the PECO filter degrades these bonds.…”
Section: Discussion: Molekule Devices To Manage Covid-19 In...mentioning
confidence: 99%
“…Life cycle analysis (LCA) and social LCA of biodegradable medical gowns [12] Green design Substituting polypropylene face masks with biodegradable polylactic acid face masks [13] Green design Development of stimuli-responsive polyelectrolyte multilayers attached to medical fibers providing cationic and anionic sites to neutral fibers and control bacterial adhesion [14] Green design Sustainable options (lower carbon footprint, design for disassembly, optimised manufacturing process, reduced energy consumption and water use during the production process) for continuous positive airway pressure therapy mask [15] Green design…”
Section: Description Of An Approach Ce Strategymentioning
confidence: 99%
“…According to the world's center for disease controls, aprons should protect arms, chest and other exposed parts of HCWs in patient care. They are used to prevent contact with pathogen-contaminated fluids and increase the sterile field of HCWs [ 21 , 22 ]. They must have some performance characteristics, such as comfort, freedom of movement to the user, flexibility, air permeability, breathability, pathogen protection barrier, liquid repellent, thermal comfort and among others [ 22 ].…”
Section: Personal Protective Equipment For Healthcare Personnelmentioning
confidence: 99%